Efficacy and Safety of Mirror Therapy for Post-stroke Dysphagia: A Systematic Review and Meta-Analysis - He, Kelin; Wu, Lei; Ni, Fengjia; Li, Xinyun; Liang, Kang; Ma, Ruijie (Frontiers in Neurology, 2022)
Background: Post-stroke dysphagia is a common symptom after stroke and one of the most frequent and severe stroke complications. Mirror therapy has recently become the research hotspot of scholars and has been investigated as a non-invasive therapeutic, rehabilitative intervention for post-stroke dysphagia in several single-centre randomised controlled trials. Objective: This study aimed to evaluate the efficacy and safety of mirror therapy for post-stroke dysphagia. Methods: Seven databases were comprehensively searched, including Pubmed, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Service System (SinoMed), Wan-fang database, and Chinese Scientific Journals Database (VIP) from inception to 31 December 2021. The primary outcome measure was efficacy as measured by clinical effectiveness rate, and the secondary outcome included the water swallow test and incidence of pneumonia. In addition, the Cochrane Risk of Bias Tool was applied to assess the risk of bias. Potential publication bias was evaluated by using Egger’s bias indicator test and visualisation of the funnel plot asymmetry. Results: Five randomised controlled trials (135 subjects in the experiments group and control groups, respectively) were identified as reporting the application of mirror therapy for post-stroke dysphagia and were included in this study. The results from our meta-analysis revealed that mirror therapy had a positive effect on clinical effectiveness rate (OR=4.26, 95%CIs=2.33;7.79) and the water-swallowing test (MD=-0.76, 95%CIs=-1.29; -0.22). Moreover, mirror therapy could reduce the incidence of pneumonia (OR=0.12, 95%CIs=0.03; 0.49). Subgroup analyses indicated that mirror therapy at the acute phase was robust, while at the convalescent phase was not stable. Sensitivity analysis revealed that these results were robust and stable. In addition, no publication bias was observed. Conclusions: The present study results indicated that mirror therapy may have a role in post stroke dysphagia management but that remains to be determined. The available trials also suggest that the evidence for the safety of mirror therapy in patients with post-stroke dysphagia is not sufficient.